2017
DOI: 10.18203/2394-6040.ijcmph20175155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal education and socioeconomic status on knowledge, attitude and practice of mother and her child regarding acute diarrhoeal diseases

Abstract: Background: In India, diarrhoea caused more than 130,000 child deaths in 2013. This also accounts for roughly one-fourth of all global diarrhoea deaths among children under five years of age. The incidence of diarrhoeal disease in rural India is 12% and in urban India is 9%.Acute diarrheal disease is both preventable and treatable. Untreated severe diarrhoea leads to fluid loss and it may be life-threatening especially in young children and among the people who are high risk like malnourished or have impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Similar findings were seen in study by Mutaliket al in Kasegaon, Maharashtra [14]. Kumaret al in their cross section study of 200 cases of age ranging from 0 -5 years having diarrhea at Kalyanpur, Bihar found Low Socio-economic status had greater impact over incidence of diarrhea [15].…”
Section: Study Conducted In 370 Under Five Children In Nemamsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings were seen in study by Mutaliket al in Kasegaon, Maharashtra [14]. Kumaret al in their cross section study of 200 cases of age ranging from 0 -5 years having diarrhea at Kalyanpur, Bihar found Low Socio-economic status had greater impact over incidence of diarrhea [15].…”
Section: Study Conducted In 370 Under Five Children In Nemamsupporting
confidence: 84%
“…The correct practice of administering ORT and HAF was found lacking in the rural community which tends to increase the severity and duration of diarrheain children. Study by Mutaliket al also reported similar findings[14]. KAP of the community can be improved by explaining and practically demonstrating the process of administering Oral Rehydration Salt and Home Available Fluidsto the members of household.…”
mentioning
confidence: 56%
“…Since mothers are the chief caregivers of children, their socioeconomic condition significantly influences the health status of their children and outcome of diarrhea episodes [ 18 ]. Lack of caregivers’ knowledge and awareness usually results in poor use of available information on preventing and managing childhood diarrhea in developing countries [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their socioeconomic condition significantly influences the health status of their children and the outcome of diarrhea episodes. 13 …”
Section: Introductionmentioning
confidence: 99%